The Effects of Exchange Rate Change on the Trade Balance in Croatia - Stucka, Tihomir (IMF Working Papers; Working Paper ;, 2004)
A reduced-form model approach was used to estimate the trade balance response to permanent domestic currency depreciation. For this purpose, long-run and short-run effects were estimated, using three modeling methods along with two real effective exchange rate measures. On average, a 1 percent permanent depreciation improves the equilibrium trade balance by between 0.94 percent and 1.3 percent. The new equilibrium is established after approximately 2.5 years. Evidence of the J-curve is also found. Overall, in the light of the results obtained, it is questionable whether permanent depreciation is desirable to improve the trade balance, taking into account potential adverse effects on the rest of the economy.